Sindrom Makan Malam, Asupan Serat, dan Pendapatan Rumah Tangga dengan Kejadian Gizi Lebih pada Siswa SMAN 6 Depok: Sindrom Makan Malam, Asupan Serat, dan Pendapatan Rumah Tangga dengan Kejadian Gizi Lebih pada Siswa SMAN 6 Depok - Putri, Salsabila Athirah; Marjan, Avliya Quratul; Sofianita, Nur Intania; Simanungkalit, Sintha Fransiske (Universitas Airlangga, 2023)
Background: The nutritional issues faced by adolescents have shifted towards the condition of overnutrition, which includes obesity and overweight. Overnutrition occurs when there is an excessive body fat accumulation, potentially increasing the risk of degenerative diseases such as hypertension, diabetes mellitus, heart disease, and others. According to Riskesdas 2018, the national prevalence of overnutrition adolescent was 13.5%. Some risk factors for the occurrence of overnutrition include genetics, psychological factors, excessive energy intake, physical activity, and socioeconomic status. Night eating syndrome is considered as a deviant eating behavior associated with overweight and obesity. Objectives: To analyze the relationship between night eating syndrome, fiber intake, and household income with the occurrence of overnutrition among students of SMAN 6 Depok. Methods: The research study design was cross-sectional. The sample was obtained using a stratified random sampling technique, resulting in 100 students from SMAN 6 Depok. Nutritional status was assessed based on body weight and height, night eating syndrome was measured using the Night Eating Syndrome Questionnaire, fiber intake was measured using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and household income was classified based on the minimum wage of Depok City. Data analysis was conducted using chi-square and fisher's exact tests. Results: The bivariate analysis revealed that night eating syndrome (p=0.004) had a significant association with the occurrence of overnutrition. Fiber intake (p=1.00) and household income (p=0.954) showed no association with the occurrence of overnutrition. Based on the multivariate analysis, night eating syndrome was found to be the most significant factor associated with overnutrition. Conclusions: Night eating syndrome is the most significant factor associated with overnutrition. Researchers suggest avoiding stress, getting enough sleep, and controlling intake, especially in the evening.